The Impact of Local Culture on the Internationalization of MSMEs: Analysis of Statue Craftsmen in Trowulan - Moch. Wahyu Widodo; Puji Handayati; Sudarmiatin Sudarmiatin (Journal Economic Excellence Ibnu Sina, 2025)
This study explores the impact of local culture on the internationalization process of Micro, Small, and Medium Enterprises (MSMEs), especially statue craftsmen in Trowulan, East Java. MSMEs in Indonesia face various challenges, including low productivity and access to technology. However, statue craftsmen in Trowulan are able to utilize the richness of Majapahit culture to differentiate their products in the global market. Using a qualitative approach through in-depth interviews and participant observation, this study found that local culture not only plays a role as a product identity, but also as a strategy to attract international consumers. Adaptation to the needs of the global market, especially in Europe, shows the ability of craftsmen to innovate and collaborate. This study provides important insights into how the integration of local culture can improve the competitiveness of MSMEs in the era of globalization, and offers recommendations to support the development of MSMEs through cultural preservation and skills improvement. The results can be used as a reference for local economic policies and the promotion of Indonesian cultural heritage.